Climate-sensitive zoonotic diseases transmissible by companion animals: A scoping review protocol - Samantha Hobson; John Mallare; Heather Grieve; J. Scott Weese; Lauren E. Grant (PLoS ONE, 2025)
Objective This joint protocol describes two scoping reviews that will identify and describe evidence for climate sensitivity of companion animal zoonotic diseases in cat, dog, and human populations worldwide. Introduction Climate change is a driver for emerging and re-emerging zoonotic diseases of global health concern. Companion animals can transmit over 70 zoonotic pathogens, some of which are sensitive to changes in meteorological factors. There is disparate evidence in our understanding of climate-sensitive companion animal zoonotic diseases. Inclusion criteria Primary research articles that describe 1) an association or effect between meteorological factors and the risk of zoonotic disease, 2) the presence of spatiotemporal variations in disease incidence or prevalence, or 3) the projected impacts of climate emission scenarios on disease trends will be included. Methods A comprehensive search strategy was developed using index terms and keywords for populations of interest, companion animal zoonotic diseases, and meteorological factors. Articles will be searched on MEDLINE (via Ovid), AGRICOLA (via ProQuest), and Web of Science. Additional articles will be identified using citation tracking. Independent reviewers will systematically apply a two-step study screening process based on defined eligibility criteria. Key study characteristics and findings will be collated and presented as a descriptive summary using graphical and tabular formats. Review registration Two separate protocols have been registered in Open Science Framework. The first review consolidates evidence in cat and dog populations (https://osf.io/ydgc2), while the second review is focused on human populations (https://osf.io/3cvx2).